(untitled) (Journal of the College of Education for Women, 2019)
A low aberration electrostatic lens of three electrode was design, Theelectrode shapes were determined using solution of Laplace equation .A new Computational technique were used to design an electrostatic lenswhich depends on the determination polynomial function of the third order withthe solution of axial - equation to find the trajectory of particles which satisfythe suggested potential function besides the other optical properties such asbrightness ,perveance and current density.The results showed low values of spherical and chromatic aberrationscomparing with other searches about1.4 for spherical aberration and 0.98 ofchromatic aberration with values of potential of 20 which are considered as goodcriteria for good lens’s design.